GAMBARAN KEPUASAN KERJA PADA GURU HONORER DI INDONESIA: LITERATUR REVIEW - Nur Imanda, Aulia; Hendriani, Wiwin (Program Studi Psikologi Fakultas Kedokteran Universitas Sriwijaya, 2020)
Honorary teachers are professionals who also support in the learning process atschool. The phenomenon that related to honorary teachers only occurs in Indonesia, wherein their duties honorary teachers have the same tasks as teachers with governmentemployees status, but the income earned by honorary teachers is far lower than teachers withgovernment employees status. This is one of the causes of honorary teachers' dissatisfactionwith their work. This study aims to determine the description of job satisfaction in honoraryteachers in Indonesia by using the literature review method based on three journals thattaken from one database, namely the Garuda Portal or the Indonesian Publication Index(IPI). Based on the three studies reviewed it can be concluded that job satisfaction withhonorary teachers has a positive relationship with other variables, namely work motivationand organizational culture. Job satisfaction can affect the performance and commitment ofhonorary teachers at their jobs. So in practice, the institution should prevent dissatisfactionwith honorary teachers from all aspects.